A radical arc in systematically documenting political context in advocacy evaluation. Issue 171 (24th September 2021) - Robinson, Nicole
Abstract: Ten major global forces are fixed within the current political context: racial capitalism, neo‐slavery, neoliberalism, white supremacy, neofascism, neocolonialism, neo‐feudalism, imperialism, corporatism, and radical imagination. These forces have been underexamined in the current advocacy evaluation practice, creating missed opportunities for evaluation as a tool for liberation. Attending to these forces and the logics underpinning them should be a new arc within the advocacy evaluation field. Expanded evaluator skills, tools, and methodologies are needed to fully assess advocacy theories of change, campaign activities, and their results in context vis‐à‐vis these 10 global forces. Several regressive field‐level processes inhibiting radical portrayals of the political context and the creation and use of liberatory metrics in advocacy evaluation are discussed.